Investigation of space-charge-limited conduction mechanisms in Fe3O4-Y-FE2O3 based on SIO2/N-type SI substrate / Nik Nadia Aina Nik Zumaihan - Nik Nadia Aina , Nik Zumaihan (2020)
In this work, thin films of functionalized Fe3O4-γ-Fe2O3 NPs deposited on n-type Si substrate was formed by self-assembly. The co-precipitation method was involved to synthesis the bare iron oxide NPs and the particles were altered to optimum pH 12 by using NH4OH. Iron oxide NPs were then undergone modification process with addition of 0.4 g oleic acid and 1.63 mmol functionalization 4-pentynoic acid. For electrical characterization of self-assembled 4-pentynoic acid functionalized Fe3O4-γ-Fe2O3 NPs on SiO2/n-Si substrate, the charge conduction mechanisms were quantitatively investigated and analyzed through the oxides for different heat treatment temperatures (70-300oC). In this study, the Ohm’s Law and PF emission were intensively investigated to identify the leakage current density of the tested materials using SigmaPlot based on J-E plot data provided. At the lower electric field, the leakage current due to Ohm’s law is the major sources contributing to oxide breakdown at the electrical breakdown field, EB level. On the other hand, the PF emission was identified and analyzed at the higher electric field before the electric breakdown occur. The highest EB was showed by the heat-treated sample of 150oC with values of 2.58×10-3MV/cm approximately at 10-3 A/cm2 and it obeys the Ohm’s law as the slope is near to 1. For dynamic dielectric constant (kr), the sample heated at 200oC showed promising value compared to other temperatures and acquired k-value (7.99) higher than commercial native oxide, SiO2 (3.8-3.9). However, its EB is considered low which limits its performance electrically. Besides, the heat-treated sample of 150oC demonstrated the best outcomes as the leakage current is low (10-3A/cm2), high EB (2.58×10-3MV/cm) and has kr near to k of SiO2 (3.85).